The professional skills of male and female educators: Problems, research and perspectives - Patrizia Sposetti; Silvia Fioretti; Giordana Szpunar; Maria Grazia Rionero; Natalia Mazzocca (Pensa MultiMedia, 2022)
Training professional skills in education are highly debated in the literature and, in recent years, in the political discussion in Italy. Educational professionalism is disciplined by Law No. 205 in 2017. This paper presents a research in progress started in the 2018-2019 academic year in two Italian universities, Sapienza University of Rome and University of Urbino Carlo Bo. During the 2019-2020 academic year, students in the third year of the Education and Training Degree course were asked to complete an online questionnaire. The questionnaire was divided into three thematic areas: a) educator's skills; b) evaluation of the university course and the connection between theory and practice; c) writing competencies. Data presented in this paper concern one of the research objectives: exploring the perception of the importance of professional skills by educators in training.